PENGARUH KUALITAS AKRUAL DAN LEVERAGE TERHADAP CASH HOLDING PERUSAHAAN - Wijaya, Anggita Langgeng; Bandi, Bandi; Hartoko, Sri (UI Scholars Hub, 2010)
This research tests the effect of accrual quality and leverage on corporate cash holding for a sample of manufacturing company listed in Indonesian Stock Exchange over the period 2006-2007. This research also tests the role of asymmetric information as a mediating variable on the relation between accrual quality and cash holding. Population of this research is 197 manufacturing companies at the Indonesian Stock Exchange. This research uses the purposive sampling method. Hypothesis test of this research employs multiple regression analysis and path analysis. The results show that: accrual quality does not affect asymmetric information; asymmetric information positively affects corporate cash holdings; asymmetric information is not a mediating variable on the relation between accrual quality and cash holding; leverage negatively affects corporate cash holding.